Controlling the dissolution of iron through the development of nanostructured Fe-Mg for biomedical applications. (1st September 2020) - Khan, Muhammad Mudasser; Deen, Kashif Mairaj; Shabib, Ishraq; Asselin, Edouard; Haider, Waseem
Abstract: In the field of biodegradable metallic materials, rapid and non-uniform biodegradation, caused by uncontrolled corrosion rates, is a potential shortcoming. Among the prominent biodegradable materials, magnesium is an attractive choice, however, it is prone to rapid dissolution. In contrast, iron possesses a slow dissolution rate. To approach the middle ground, instead of making magnesium more corrosion-resistant, the less-explored approach of making iron less corrosion-resistant is employed here. In this study, iron, and magnesium, having contrasting corrosion rates, are combined via magnetron co-sputtering. The idea of combinatorial synthesis is employed to fabricate two model nanostructured Fe-Mg samples, i.e. CSFM-1 (Fe85 Mg15 ), and CSFM-2 (Fe65 Mg35 ), exhibiting a controlled and uniform degradation in phosphate-buffer saline solution. The structural characterization of the two samples demonstrates a substitutional solid solution of bcc-Fe—Mg in CSFM-1 and an amorphous short-range-ordered structure in the CSFM-2 sample. Electrochemical investigation shows increased corrosion rates for the two Fe-Mg samples in comparison to pure Fe, validated by relatively active corrosion potentials, higher corrosion current densities, faster anodic dissolution, and lower charge transfer resistances, governed by chemical composition and non-equilibrium nanostructures. Finally, nano-indentation testing of the two samples reveals relatively higher hardness and lower elastic moduli, a suitable combination for bio-implants. Statement of Significance: The use of Mg as a biodegradable in-vivo  implant material is problematic because of its high dissolution rate and potential for hydrogen gas generation. This is the first time that the idea of combinatorial synthesis is employed to fabricate two model nanostructured Fe-Mg systems, i.e. CSFM-1 (Fe85 Mg15 ), and CSFM-2 (Fe65 Mg35 ), exhibiting a controlled and uniform degradation. The structural characterization of the two systems demonstrates a substitutional solid solution of bcc-Fe—Mg in CSFM-1 and an amorphous short-range-ordered structure in the CSFM-2 system. Electrochemical investigation shows increased biodegradation rates for the two Fe-Mg systems in comparison to pure Fe, validated by relatively active corrosion potentials, higher corrosion current densities, faster anodic dissolution, and lower charge transfer resistances, governed by chemical composition and non-equilibrium nanostructures. Graphical abstract: Image, graphical abstract